Kinetic Aggregation And Settling Properties Of Silicon Dioxide Nanoparticles In Chemical Mechanical Polishing Synthetic Wastewater - Azman, Nur Athirah Nor (Universiti Sains Malaysia, 2022)
The semiconductor industry is one of the most favoured industries around the world as the demands for manufacturing the semiconductor product, microchips, as well as electronic devices such as telephones, television, etc. keep increasing year by year. Due to this scenario, numerous nanoparticles were present in the CMP wastewater that easily suspended and surpass the filtration process. The disposal of nanoparticles can enter the water bodies and affect the environment. Thus, an understanding of the characteristics of pollutants especially nanoparticles in the CMP wastewater needs to be taken as an important part before treating the waste. The synthetic nanopowder silicon dioxide (SiO2) has been used in this study with the size of 0.1 mm. The SiO2 NP solution was prepared for different suspensions (25, 50 and 100 mg/L) for the characterization of SiO2 in terms of stability of pH, zeta potential and z-average hydrodynamic diameter at various pH. From this analysis, I can conclude that the zeta potential and the particle size of SiO2 are relatively directly proportional to the pH range from pH 2 to pH 12. The SiO2 suspension of 100 mg/L was found to have a close to the zero-negative charge of -2.98 mV with particle size 277.6 d.nm at pH 2.47. Then it was analysed in function of time to evaluate the stability of the particle at various pH. Next, the experiment was continued to analyse the characteristic behaviour of 100 mg/L of SiO2 nanoparticles suspension with the presence of 10-3 M NaCl and 0.15 M NaCl. These two ionic strengths were used for the simulation of river and seawater to study the behaviour of the nanoparticles when they are being released into the environment. Consequently, the addition of NaCl affects the zeta potential and z-average hydrodynamic diameter of the SiO2 nanoparticles. The zeta potential increase to positive values as well as increases the particle size of the nanoparticles which is +0.6 mV with 766.1 d.nm for SiO2 + 10-3 M NaCl, and +0.037 mV with 1198 d.nm for SiO2 + 0.15 M NaCl.